2017
DOI: 10.1177/0958305x17739475
|View full text |Cite
|
Sign up to set email alerts
|

Household cooking fuel use patterns and determinants across southern Africa: Evidence from the demographic and health survey data

Abstract: Improving access to modern energy sources is critical to enhancing the quality of life of many people in developing countries. In southern Africa, the majority of rural and poor urban households are dependent on solid fuels to meet their cooking needs. To date, there is scarce information in the literature on household cooking fuel patterns across southern Africa. Using household fuel data from the Demographic and Health Survey, this study investigated cooking fuel types and the determinants of their choice by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 57 publications
9
50
1
Order By: Relevance
“…In both rural and peri-urban homes, level of education was independently associated with use of LPG with a ‘dose–response’ relationship between increasing level of education and an increasing likelihood to use any LPG (rural and peri-urban) and an exclusive LPG (peri-urban). The importance of education in the transition to modern and cleaner cooking fuels is well documented (Makonese et al 2017; Mekonnen and Kohlin 2008; Nlom and Karimov 2015). In their analysis of determinants of household cooking fuels across Southern Africa, Makonese et al (2017) found education to be an important predictor of type of primary cooking fuel in Lesotho, Namibia, Swaziland, Zambia and Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both rural and peri-urban homes, level of education was independently associated with use of LPG with a ‘dose–response’ relationship between increasing level of education and an increasing likelihood to use any LPG (rural and peri-urban) and an exclusive LPG (peri-urban). The importance of education in the transition to modern and cleaner cooking fuels is well documented (Makonese et al 2017; Mekonnen and Kohlin 2008; Nlom and Karimov 2015). In their analysis of determinants of household cooking fuels across Southern Africa, Makonese et al (2017) found education to be an important predictor of type of primary cooking fuel in Lesotho, Namibia, Swaziland, Zambia and Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of education in the transition to modern and cleaner cooking fuels is well documented (Makonese et al 2017; Mekonnen and Kohlin 2008; Nlom and Karimov 2015). In their analysis of determinants of household cooking fuels across Southern Africa, Makonese et al (2017) found education to be an important predictor of type of primary cooking fuel in Lesotho, Namibia, Swaziland, Zambia and Zimbabwe. Education is important in promoting the benefits of clean energy, clean fuels and the health implications of using traditional fuels for cooking, and the authors suggest that better education for household heads, promotion of efforts to specifically target less educated populations and tailoring educational materials appropriately would create a shift reducing the chances of choosing traditional fuels over modern cleaner options such as LPG and electricity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of energy efficiencies, costs and factors is important in the southern African context. For example, 66% of households in southern Africa depend on cheap fuel sources such as fuelwood (Makonese et al, 2018). Although electrification has increased, most households cannot afford the appliances or the monthly electricity costs and continue to use cheaper fuels (Davis, 1998;Howells et al, 2005).…”
Section: Some Implications For the South African Contextmentioning
confidence: 99%
“…There is an emerging challenge of providing cleaner fuel to household to avoid various health risks arising from the use of traditional non-cleaner fuel and to cope with the challenges created by climate change (WHO, 2018).Household fuel choices are determined by a wide range of socio-economic factors (Lusambo, 2016;Giri & Goswami, 2018;Makonese et al, 2018;Rathore & Chauhan, 2018). There is a growing interest on cleaner and convenient fuels against traditional fuels such as biomass that is primarily dominated by firewood.…”
Section: Introductionmentioning
confidence: 99%